5-deoxy-rutaecarpine protects against LPS-induced acute lung injury via inhibiting NLRP3 inflammasome-related inflammation - Luo, Jinque; Li, Xin; Zhang, Li; Deng, Meijing; Zhao, Jieyang; Zhang, Jinghuan; Tang, Wenyu; Guo, Qinghua; Wang, Ling (Frontiers in Pharmacology, 2025)
IntroductionAcute lung injury (ALI) induced by lipopolysaccharide (LPS) is a significant medical condition characterized by severe pulmonary inflammation and tissue damage. NLRP3 inflammasome-driven inflammation is essential in ALI pathogenesis, inspiring novel therapeutic strategies that focus on NLRP3 and inflammation. In this study, we investigated the therapeutic potential of 5-deoxy-rutaecarpine (5-DR), a rutaecarpine derivative, in attenuating LPS-induced ALI.MethodsIn this study, we evaluated the effects of 5-DR treatment in mice exposed to LPS, lung tissues, bronchoalveolar lavage fluid, and serum were collected for analysis. LPS-stimulated J774A.1 mouse macrophages were used to further investigate the anti-inflammatory effects of 5-DR in vitro. Various techniques including histopathology, Western blotting, and luciferase reporter assay were employed.Results5-DR treatment significantly reduced lung edema, inflammatory cell infiltration in mice with LPS burden, and reduced the levels of inflammatory mediators like interleukin-1β in the mice and in LPS-stimulated J774A.1 mouse macrophages. Further western blotting analysis showed 5-DR decreased the levels of NLRP3, cleaved caspase-1, and mature IL-1β in mice and J774A.1 cells exposed to LPS. Additionally, NF-κB pathway activation significantly diminished the inhibition of the NLRP3 inflammasome by 5-DR.DiscussionOur findings highlight the therapeutic potential of 5-DR as a promising candidate for treating LPS-induced ALI, offering insights into its underlying mechanism that targets NLRP3 inflammasome-mediated inflammation.